'A more creditable way': The discovery of active sonar, the Langevin–Chilowsky patent dispute and the Royal Commission on Awards to Inventors. (January 2018) - Zimmerman, David
On 19 July 1926, the Royal Commission on Awards to Inventors held a hearing on the claim of Professor Paul Langevin and Monsieur M. Constantin Chilowsky for compensation from the British Admiralty for their discovery of sonar. The hearings provide unique insights into the origins and early research of active sonar and an important snapshot of the Royal Navy's anti-submarine warfare research in the mid-1920s. Moreover, the hearing reveals much more than the details of a major technological discovery; it is also an important case study of the relationship between inventors and governments during and after the First World War.